The Impact of agricultural expenditure on economic growth in Sub Saharan African countries (SSA) - WEOLEBO, Tizita Feleke (KDI School, 2018)
This study to examine the impact of agricultural expenditure on economic growth of sub Saharan Africa region. The study used secondary data source from the World Bank(WB) development indicator for the period between 1990-2015.The study employed OLS regression and Panel Fixed effect model. The findings revealed that expenditure on agriculture, health and education has a positive and significant effect on GDP per capital of the region. Public spending on agriculture was strong in promoting economic growth in SSA. Because agriculture is a primary economic base for many African countries. Hence, the study recommended that the government should increase expenditure on agriculture, health and education to promote economic growth. Thus, the results suggest that the allocation of government expenditure towards agricultural sector should be favored in order to enhance sustainable economic growth.
Thesis(Master) --KDI School:Master of Public Policy,2018